Peran corporate social responsibility terhadap loyalitas anggota di Koperasi Peternak Sapi Perah (KPSP) Setia Kawan - Khoirot, Naila Dzul (Maliki Interdisciplinary Journal, 2023)
This article discusses the importance of implementing corporate social responsibility (CSR) carried out by cooperatives on members satisfaction. CSR can be interpreted as a company’s awareness of the responsibilities they have towards the surrounding environment, such as economic, legal law, ethical, and social, especially the responsibilities to stakeholders. The cooperative discussed in this article is Koperasi Peternak Sapi Perah (KPSP) which is located in Tutur District, Pasuruan Regency. This cooperative has a core business of storing and selling fresh milk. KPSP Setia Kawan implements CSR programs in its business. This article describes several CSR programs implemented by KPSP Setia Kawan. The implementation of CSR can make cooperative members feel that they are given attention and cared for. This can have positive impacts if it is carried out continuously and with commitment. The costs incurred by cooperatives for CSR programs can be long-term investments that can bring many benefits to cooperatives itself. The impact of the implementation of CSR programs on KPSP Setia Kawan is increasing the loyalty of its members. Member loyalty is a valuable asset that can make KPSP Setia Kawan maintain its existence in the corporate world.